Antidiarrheal and antispasmodic activities of Vitex negundo are mediated through calcium channel blockade (Bangladesh Journal of Pharmacology, 2013)
Vitex negundo has reputation in the traditional medicine in diarrhea and gut spasm. This study was carried out to provide possible pharmacological basis to its medicinal use in hyperactive gut disorders. In castor oil-induced diarrheal model, the crude extract of V. negundo, caused a dose-dependent protection (53-71%), similar to loperamide. In isolated rabbit jejunum preparation, V. negundo caused inhibition of spontaneous and high K+-induced contractions, with EC50 values of 0.36 (0.22-0.61) and 1.30 mg/mL (0.27-5.89; n=4-5), respectively, suggestive of spasmolytic activity, mediated possibly through calcium channel blockade (CCB). The CCB activity was further confirmed when pre-treatment of the tissue with V. negundo (0.03-0.3 mg/mL) caused a rightward shift in the Ca++ concentration-response curves (CRCs), similar to diltiazem or loperamide.  These data indicate that the antidiarrheal and spasmolytic effects of the crude extract of V. negundo are mediated through the presence of CCB-like constituent(s).